Geographic information system assisted (GIS-assisted) tourism destination management development of a spatial database for Narra, Palawan - Parca, Marie Felipe B.
This study presents how Geographic Information System (GIS) can be utilized for tourism destination management, specifically tourism resource inventory, analysis and modelling. GIS functions like data collection, storage and processing are employed to build a tourism spatial database containing various tourism points of interest (attractions, accommodations, amenities and accesses). These points of interest are integrated with their corresponding geographical attributes. Spatial database query demonstrates GIS' ability to access and extract tourism information potentially enhancing tourism experience. This enhanced access to tourism information allows for easy data processing, analysis and presentation. Geographic analysis is carried out to show the relationships of tourism points of interest and simulate accessibility and various tourism phenomena. The analyses includes spatial statistical analysis such as central feature analysis and average nearest neighbour analysis and network analysis such as service area analysis, closest facility analysis, routing analysis and origin and destination cost matrix analysis. The results show that GIS can be useful for the tourism industry by providing the basis for tourism destination management and by means of the tourism applications that can be developed using the technology. Essential locations for potential tourism features and tourism development are determined. Visualization, planning and simulation of access to tourism destinations and facilities provide information on accessibility and directions giving way for the generation, suggestion and custornization of tourism routes. Overall, GIS technology not only integrates common database operations with unique visualizations but also offers geographic analysis that can aid in decision making for management and future planning.